Standardized metrics to quantify solar energy-land relationships: A global systematic review - Cagle, Alexander E.; Shepherd, Morgan; Grodsky, Steven M.; Armstrong, Alona; Jordaan, Sarah M.; Hernandez, Rebecca R. (Frontiers in Sustainability, 2023)
Ground-mounted solar energy installations, including photovoltaics (PV) and concentrating solar power (CSP), can have significant environmental, ecological, and sociocultural effects via land-use and land-cover change (LULCC). Research in disciplines ranging from engineering to environmental policy seeks to quantify solar energy-land (SE-land) interactions to better understand the comprehensive impacts of solar energy installations on society. However, increasing evidence shows that scholars across research disciplines employ disparate metrics to quantify SE-land interactions, possibly preventing the dissemination and aggregation of trends across the literature. While solar energy deployment helps to achieve progress towards sustainable development goal (SDG 7- affordable and clean energy), inconsistent metric use for SE-land interactions may inhibit the understanding of the total environmental and ecological impacts of solar energy installations, potentially causing barriers to achieve concurrent SDG’s such as life on land (SDG 15). We systematically reviewed 608 sources on SE-land relationships globally to identify and assess the most frequent metric terms and units used in published studies. In total, we identified 51 unique metric terms and 34 different units of measure describing SE-land relationships across 18 identified countries of author origin. We organized these findings into three distinct metric categories: 1) capacity-based (i.e., nominal), 2) generation-based, and 3) human population-based. We used the most frequently reported terms and units in each category to inform a standardized suite of metrics, which are: land-use efficiency (W/m2), annual and lifetime land transformation (m2/Wh), and solar footprint (m2/capita). This framework can facilitate greater consistency in the reporting of SE-land metrics and improved capacity for comparison and aggregations of trends, including SE-land modeling projections. Our study addresses the need for standardization while acknowledging the role for future methodological advancements. The results of our study may help guide scholars towards a common vernacular and application of metrics to inform decisions about solar energy development.